Men without hats : dialogue, discipline, and discontent in the Madras army 1806-1807 - Hoover, James W. (New Delhi : Manohar Publishers & Distributors, 2007)
Chiefly on Vellore Mutiny, 1806 and Madras Army during Bristish India.
Includes bibliographical references (p. [297]-305) and index.
Keywords: East India Company. -- Army. -- Madras Army -- History; Vellore Mutiny, Vellore, India, 1806.; Madras (India : Presidency) -- Politics and government